Intelligent Drug Delivery System Using UML Diagrams Analysis - 崔琦峰 刘成良 ZHA Xuan F (Shanghai jiao tong da xue xue bao, 2008)
A novel intelligent drug delivery system potential for the more effective therapy of the diabetics was proposed, and the composition of system was analyzed. Based on the design of micro-electro-mechanical systems （MEMS）, an iterative modeling process was introduced. Unified modeling language （UML） was employed to describe the function requirement, and different diagrams were built up to explore the static model, the dynamic model and the employment model. The mapping analysis of different diagrams can simply verify the consistency and completeness of the system model.